2018
DOI: 10.1371/journal.pone.0208982
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Receptor Nicotinic Alpha 5 (CHRNA5) RNAi is associated with cell cycle inhibition, apoptosis, DNA damage response and drug sensitivity in breast cancer

Abstract: Cholinergic Receptor Nicotinic Alpha 5 (CHRNA5) is an important susceptibility locus for nicotine addiction and lung cancer. Depletion of CHRNA5 has been associated with reduced cell viability, increased apoptosis and alterations in cellular motility in different cancers yet not in breast cancer. Herein we first showed the expression of CHRNA5 was variable and positively correlated with the fraction of total genomic alterations in breast cancer cell lines and tumors indicating its potential role in DNA damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 91 publications
(113 reference statements)
0
7
0
Order By: Relevance
“…CpG site-annotated genes such as SAPCD2 are critical in the progression of cancers and cardiovascular diseases [ 39 ]. A previous report suggested that CHRNA5 RNAi was associated with cell cycle inhibition, apoptosis, reduced DNA damage response, and increased drug sensitivity in breast cancer [ 40 ]. CHRNA5 (15q25.1) is localized in lung cancer susceptibility loci, and CHRNA5 polymorphism is related to lung cancer susceptibility [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…CpG site-annotated genes such as SAPCD2 are critical in the progression of cancers and cardiovascular diseases [ 39 ]. A previous report suggested that CHRNA5 RNAi was associated with cell cycle inhibition, apoptosis, reduced DNA damage response, and increased drug sensitivity in breast cancer [ 40 ]. CHRNA5 (15q25.1) is localized in lung cancer susceptibility loci, and CHRNA5 polymorphism is related to lung cancer susceptibility [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as α4β2α5 nicotinic receptors support higher conductance of calcium ions into the cell (Scholze & Huck, 2020; Sciaccaluga et al, 2015), another putative neuroprotective mechanism of the α5 subunit may be through driving possible calcium-dependent pro-survival pathways in the neurons which express the α4β2α5 nicotinic receptors (Cingir Koker et al, 2018; Ueda et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The expression profile of nAChR subunits is different in subtypes of breast cancer [ 12 ]. The nAChRα5 associates with cell cycle, apoptosis, and DNA damage response of luminal-type breast cancer cells [ 13 ]. The nAChRα7 promotes cell proliferation and apoptosis in a panel of breast cancer cell lines [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of nAChR subunits are different on breast cancer cell lines [ 12 ]. It is reported that nicotine acts on breast cancer cells such as luminal- and TNBC-type via some nAChRs [ 13 21 ]. However, the nicotine-mediated biological effects including the regulation of immune-check point molecules on HER2-type breast cancer cells are largely unknown.…”
Section: Introductionmentioning
confidence: 99%